Immunocytochemistry in lung fine needle aspiration cytology: comparison of four protocols - Santos, Bruna (2022)
Background – Long-term preservation of fine-needle aspiration cytology slides is an essential requirement in cytopathology laboratories for the eventual performance of immunocytochemistry. ICQ contributes to a correct and complete diagnosis, considering that long-term morphological and antigenic preservation is essential to obtain reliable results. In this study, we intend to evaluate and compare the immunoexpression of TTF1, p40, and chromogranin A antigens in lung samples taken from the archive and stained with: i) Papanicolaou (Pap); ii) May-Grünwald Giemsa (MGG); iii) preserved in polyethylene glycol (PEG); and iv) processed as cell-block. Methods – Twenty-four fine needle aspiration cytology samples diagnosed as primary lung carcinoma with a sample processed by each of the protocols studied (Pap, MGG, PEG, and CB) were selected from the archive. Based on the diagnosis, immunostaining was performed with primary antibodies anti-TTF1 (adenocarcinomas), anti-p40 (squamous cell carcinomas), and anti-chromogranin A (neuroendocrine carcinomas). The quality of immunostaining was evaluated by two independent observers using an evaluation grid (rated from 0 to 27 points) that comprises parameters as: morphological preservation, specific staining intensity, sensitivity, specificity, and contrast. Results – The mean values obtained for CB, PEG, Pap, and MGG protocols were 21.58 (±4.54), 11.79 (±1.88), 22.25 (±5.30), 26.31 (±1.21) points respectively. CB achieved better results when compared to other protocols under study (p<0.05). When compared in pairs (Tuckey post-hoc) the only protocols that did not show statistically significant differences were Pap and PEG (p=0.0814). Conclusions – Cell-block is the elected protocol to perform ICQ for the samples and antigens under study. The Pap and PEG protocols showed loss of immunostaining, which could lead to false-negative results. Immunostaining was not observed in any sample with MGG protocol.